Restructuring maternal services during the covid-19 pandemic: Early results of a scoping review for non-infected women. (March 2021) - Montagnoli, Caterina; Zanconato, Giovanni; Ruggeri, Stefania; Cinelli, Giulia; Tozzi, Alberto Eugenio
Highlights: Anti-pandemic norms cause a reduction of antenatal care in-person visits. Integrating fewer consultations with telemedicine may be the solution to guarantee essential services and appropriate maternal care. New health strategies apply to women with low-risk pregnancies, while the hospital centered assistance is maintained for complicated obstetric cases. Interdisciplinary collaboration of medical, administrative and informatic resources is warranted to implement virtual forms of antenatal care. Abstract: Introduction and objective: The novel coronavirus outbreak has caused substantial changes in societal norms as well as adjustments in health systems worldwide. To date the impact of these pandemic-related variations has yet to be fully understood also in the field of maternal health for which continuity of care is a proven life-saving preventive measure. Design: Following the PRISMA guidelines for reviews, a literature search was carried out to assess different approaches that combine quality of maternal care with the imposed social-distancing rules. Nine studies were included in the scoping review. Findings: Reduction of in-person visits is the preferred overall solution. Yet, fewer consultations can still guarantee essential services and appropriate care through integration with telemedicine. Referral to epidemic-free community centres is an alternative option and new paths need to include the interdisciplinary contribution of medical consultants and IT experts, among others. In this context, delaying access for symptomatic expectant mothers is still debated since it carries the potential risk of untimely detection of pregnancy complications. Key conclusions: Preliminary experiences provide an overview of the different attempts put in place to reshape health services to contain the pandemic hazards. Implications for practice: These early prototypes may inspire future innovative health solutions compatible with local resources and specific population preferences and needs.